Approbation of a structural approach mode for optimization producing coatings, increases the wear resistance of the turbine blades - Соболь, Олег Валентинович; Дмитрик, Виталий Владимирович; Погребной, Николай Андреевич; Пинчук, Наталия Владимировна; Мейлехов, Андрей Александрович (Eastern-European Journal of Enterprise Technologies, 2015)
A complex analysis of the benefits of using a vacuum-plasma coatings to increase wear steam turbine components. The possibility of using a structured approach to surface engineering to monitor the efficiency used in the preparation of coatings, physical and technological parameters. As express structural parameters control the functional properties of the nitride coating with an fcc crystal lattice is proposed to use the degree of texturing to the [111] axis perpendicular to the growth surface, and the average size of the crystallites. It is shown that the use of high-voltage pulse stimulation technology to streamline the formation mononitride coatings, as well as multi-element nitrides highentropy alloys can increase the hardness of coatings by more than 1.5 times, and the abrasion resistance increased more than 1.7 times, compared with coatings currently used to protect the blades from wear and friction-slip gas turbine units.